IMPLEMENTASI KONTROL OTOMATIS PAKAN IKAN DAN PENERANGAN TAMAN BERBASIS ARDUINO DI SMPN 10 SALATIGA - Suhartono, Bambang; Jaelani; Dwi Setiawan (Jurnal Ilmiah Sistem Informasi, 2022)
Electrical equipment plays an important role in everyday life, from households, schools, hotels, offices, to industrial environments. Because it really helps humans in making work easier. The need for automated tools to facilitate human activities, makes the need for smart chips or microcontrollers increasing. A new breakthrough in the world of microcontrollers with the application of Arduino.Especially at SMPN 10 Salatiga, there are fish ponds and garden lights, which you forget to feed or not, while the officers forget to turn off the lights, causing the fish to die and the lights stay on even though it is noon. This study tries to implement Fish Feed Control and automatic garden lights on and off using Arduino and scheduling, this is so that the fish stay healthy and the garden lights can turn on or off according to the schedule desired by management. The author designed a garden lamp and automatic fish feed based on a case study at the school. The tool is designed with three sources of tool control. The first manual is pressing the fish feed manual button, the light switch and the reset button. Both semi-automatic, as a fish feeder, light ON/OFF and reset remote control with the Android application. The third auto is scheduled feeds and lights. This tool is designed to manage fish feed and garden area lighting. This tool is practical to use, inexpensive, useful, flexible and easy to build. The classification of this tool is sufficient for the needs of the school garden. Among the advantages of this tool is that it can be controlled remotely effectively 25 m without a hitch using the android application. The author hopes, this tool provides benefits and solves problems in schools.